2021
DOI: 10.1039/d0nj04735j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2′-(1,2,3-triazoyl)-acetophenones: molecular docking and inhibition ofin vitromonoamine oxidase activity

Abstract: The synthesis of 2′-(1,2,3-triazoyl)-acetophenones by a CuAAC using thiourea as a ligand, molecular docking and MAO activity analyses were performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…A previous study has shown that ETAP has the ability to inhibit MAO, an enzyme responsible for the degradation of the biological monoamines serotonin, norepinephrine, and dopamine. The results presented by Costa are in line with the data published by Singh, which demonstrated that compounds from the 1,2,3-triazole class are involved in the inhibition of MAO. MAO is found in two isoforms in the organism, MAO-A and MAO-B, with MAO-A being the isoform that has the highest affinity for degrading serotonin and MAO-B has a higher affinity to dopamine .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study has shown that ETAP has the ability to inhibit MAO, an enzyme responsible for the degradation of the biological monoamines serotonin, norepinephrine, and dopamine. The results presented by Costa are in line with the data published by Singh, which demonstrated that compounds from the 1,2,3-triazole class are involved in the inhibition of MAO. MAO is found in two isoforms in the organism, MAO-A and MAO-B, with MAO-A being the isoform that has the highest affinity for degrading serotonin and MAO-B has a higher affinity to dopamine .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the class of 1,2,3-triazoles has been considered promising due to the variety of pharmacological properties it presents, such as the ability to form covalent and hydrophobic interactions with different pharmacological targets . Additionally, this class of compounds exhibits surfactant properties, which allows for binding to different pharmacophores, triggering or blocking biological responses, and making this class an interesting alternative for the development of synthetic drugs. , Among the various activities found, the class of 1,2,3-triazoles has demonstrated evidence of antidepressant activity, as it has been shown to be involved in the inhibition of serotonin reuptake and the inhibition of monoamine oxidase (MAO) enzyme, two mechanisms observed in known antidepressants. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, three research groups from Universidade de Pelotas (Brazil), led by Brüning and Alves [45] , described the synthesis of 2′-(1,2,3-triazoyl)-acetophenones ( 126 ) by copper catalyzed azide-alkyne cycloaddition of 2′-azidoacetophenone ( 124 ) with alkynes ( 125 ) ( Scheme 34 ). The corresponding acetophenones ( 126 ) were obtained in moderated to excellent yields under mild conditions in the presence of catalytic amount of copper iodide as catalyst and thiourea as ligand using conventional heating or ultrasound energy.…”
Section: Ultrasound-assisted Organic Synthesismentioning
confidence: 99%